Comparison of experiment and models of geodesic acoustic mode frequency and amplitude geometric scaling in ASDEX Upgrade. (11th March 2016) - Simon, P; Conway, G D; Stroth, U; Biancalani, A; Palermo, F
Abstract: In a set of dedicated ASDEX Upgrade shape-scan experiments, the influence of plasma geometry on the frequency and amplitude behaviour of the geodesic acoustic mode (GAM), measured by Doppler reflectometry, is studied. In both limiter and divertor configurations, the plasma elongation was varied between circular and highly elongated states ( ). Also, the edge safety factor was scanned between 3  <   q   <  5. The GAM frequency and amplitude are used to test several models (heuristic, fluid and gyrokinetic based), which incorporate various plasma geometry effects. The experimentally observed effect of decreasing with increasing κ is predicted by most models. Other geometric factors, such as inverse aspect ratio ε and Shafranov shift gradient are also seen to be influential in determining a reliable lower boundary. The GAM amplitude is found to vary with boundary elongation and safety factor q . The collisional damping is compared to multiple models for the collisionless damping. Collisional damping appears to play a stronger role in the divertor configuration, while collisional and collisionless damping both may contribute to the GAM amplitude in the limiter configuration.